The The initiation rite of university hazing in the city of Soria, Spain - Hamodi Galán, Carolina (2023)
Objective. The aim of this study was to deepen our knowledge of the phenomenon of hazing in the university context in Soria, analyzing it from a gender perspective. Methods. A survey was applied to the students of the University of Valladolid (Soria Campus), with a statistically significant sample. Descriptive statistics were used for the analysis with general percentages and disaggregated by gender (using the gender gap as an indicator). Results. The results seem to show that, in the context of Soria, hazing is not, in general, a phenomenon of violation of rights for students. They are valued positively above all because they allow students to get to know their classmates and the majority support their persistence. However, this study cannot ignore the fact that, although it is a very small proportion of students, there are those who have felt uncomfortable, forced, etc., during the hazing process. Likewise, there are differences according to gender that make visible the sexism that exists in society. Conclusions. It is essential to delve into the discourses of those who have felt violated by means of qualitative research techniques. It is recommended to propose safe alternatives, such as welcome days or integration activities.